Sattelite Data for Fish Concentration Identification in Marine - Santoso, Sugiharto Budi (Forum Geografi, 1996)
Knowledge shortcoming in fish-living management as well as marine biotic living cycle and fishermenâs fault technology capability causes their inadequate skill to catch fishes in large scale. To increase the result of caught fishes, it necessary to give the fishermen suffice technology of when and where the shool of fishes site in the sea. Recognizing the school of fishes in the sea is guided with the satellite data of NOAA, GOES, ADEOS as well as Landsat and the others which are able to point the site of where fishes are schooling. Besides, by making use of GPS satellite the position of fishermenâs ship then could be detected so that the movement ould be easily observed.